Avaliação da resposta imunológica a peptídeos sintéticos mimetopos de proteínas totais de larvas do carrapato Boophilus microplus (Acari: ixodidae) em camundongos e bovinos - Marra, Andréa de Oliveira Marques (2004)
The Boophilus microplus tick is one of the most important arthropods that can parasitize bovines, causing great damages to the world livestock through direct and indirect effects. The application of chemical products is the principal method of controlling this parasite, but in function of the disadvantages of this practice, the use of vaccines is a good alternative, because they are residue free, specifics and present smaller possibility to develop resistance. With the objective of selecting synthetic peptides expressed in the capsid of phage display bacteriophages, it was produced the serum policlonal in chickens previously sensitized with total larva proteins of the Boophilus microplus tick. The peptides found in larger frequency and with larger antigenic index (bioinformatics and dot blotting with chicken serum) were selected for the immunization of mice and bovines. The initial data infer that the peptides in phagos induced immune response, evaluated by Elisa test, and the more immunogenic are: 2D7 (SNNADYKQSLL), 2E6 (VNWNSWHKTNLS), 2F3 (SIPTYTPDKVTY) and 2E4 (DAWKMRLSQMYD). The sequences selected in the present work introduce the protean motives NxxxKxxL (2D7, 2E6 and 2E4) and the motive TPDKS (2E4). These sequences presented structural similarities with some tick proteins, mainly the calreticulin. Complementary studies are being accomplished to characterize the sensibility and specificity to the selected peptides.